2008
DOI: 10.1080/03008200801913338
|View full text |Cite
|
Sign up to set email alerts
|

MT3-MMP (MMP-16) is Downregulated byIn VitroCytokine Stimulation of Cartilage, but Unaltered in Naturally Occurring Equine Osteoarthritis and Osteochondrosis

Abstract: Matrix degradation by metalloproteinases is considered a key feature in the loss of articular cartilage seen in many joint diseases. Membrane-type matrix metalloproteinase-3 (MT3-MMP) expression is elevated in human cartilage in end-stage osteoarthritis. We investigated whether MT3-MMP is similarly regulated in cartilage in two naturally occurring arthropathies in vivo and whether proinflammatory cytokines regulate its expression in vitro. MT3-MMP expression was evaluated in cartilage from horses with osteoart… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 54 publications
1
6
0
Order By: Relevance
“…Consistent upregulation of ADAMTS-5 expression in IL-1β-treated pellets in this study differs somewhat to the results by Little et al [13], where IL-1β-induced ADAMTS-5 expression was detected in metacarpophalangeal but not in carpal cartilage explants. However, our finding of increased MMP-13 expression after IL-1β treatment is in agreement with other equine studies [10][11][12][13][14][15]. In accordance with Little et al [13], who did not detect overall site-related differences in response to cytokine treatment (although individual variation was found), topographical differences in this study were only found for aggrecan expression after IL-1β treatment.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Consistent upregulation of ADAMTS-5 expression in IL-1β-treated pellets in this study differs somewhat to the results by Little et al [13], where IL-1β-induced ADAMTS-5 expression was detected in metacarpophalangeal but not in carpal cartilage explants. However, our finding of increased MMP-13 expression after IL-1β treatment is in agreement with other equine studies [10][11][12][13][14][15]. In accordance with Little et al [13], who did not detect overall site-related differences in response to cytokine treatment (although individual variation was found), topographical differences in this study were only found for aggrecan expression after IL-1β treatment.…”
Section: Discussionsupporting
confidence: 94%
“…IL-1 has been shown to induce gene expression of matrix-degrading enzymes in equine chondrocytes [10][11][12][13][14][15], inhibition of proteoglycan synthesis [16][17][18][19], and increased release of glycosaminoglycans from cartilage explants [13,16,[19][20][21]. In addition, using cDNA array on equine monolayer chondrocytes, over 100 modulated transcripts were identified after brief exposure to IL-1β [14].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, gene expression is significantly downregulated by the addition of recombinant human interleukin-1b, oncostatin M, or tumor necrosis factor-a to normal cartilage explants (Garvican et al, 2008).…”
Section: Neoplastic Diseasesmentioning
confidence: 99%
“…Osteoarthritis (OA), also known as hypertrophic arthritis, is a degenerative joint disease and has become a prevalent clinical disorder in the elder [ 21 ]. Research has shown that many growth factors, cytokines and enzymes such as Interleukin (IL)-1β [ 22 ], metalloproteinases (MMPs) [ 23 ], inhibitors of metalloproteinase (TIMP)-1 [ 24 ] and collagenase [ 25 ] are closely related to the pathogenesis of OA. In addition, angiogenesis has been suggested to play important role in degeneration of articular cartilage after OA, and the level of vascular endothelial growth factor (VEGF) in OA cartilage is increased [ 26 ].…”
Section: Introductionmentioning
confidence: 99%